PLANT SPECIES MAPPING AND DENSITY IN THE VILLAGE FOREST OF PENGLIPURAN, BANGLI, BALI, INDONESIA AND ITS USE IN LEARNING MEDIA - Wijana, Nyoman; Setiawan, I Gusti Agung Nyoman (International Journal of Natural Science and Engineering, 2017)
The objectives of this research are to acknowledge the relative density index of plant species and the distribution of the plant species in the village forest of Penglipuran, Bangli, Bali, Indonesia, and (2) the utilization of his research results in instructional media. The population of this study is the whole area of Penglipuran village forest and all the plant species in it. The samples of this study are all plant species covered in 100 quadratics of size 10x10m. The sampling technique used is systematic sampling. The data are analyzed descriptively. Population utilization of research result in instructional media use student of Department of Biology Education FMIPA Undiksha, Semester V class A, B, and C. The sample is student class V class A with number of student counted 25 people. The sampling technique is by using random sampling technique. The method of data collection is interview and observation. The data are analyzed descriptively. Result of this research are (1) The plant species distribution mapping result shows that the plant species have wide, medium, and narrow distribution. (2) From the 34 species which are included into 21 families, 10 of them have the highest relative density index. (3) The results of this research can be used as a media in learning Biology, especially in Plant Ecology